First-passage duality. (26th September 2018) - Krapivsky, P L; Redner, S
Abstract: We show that the distribution of times for a diffusing particle to first hit an absorber is independent of the direction of an external flow field, when we condition on the event that the particle reaches the target for flow away from the target. Thus, in one dimension, the average time for a particle to travel to an absorber a distance away is, independent of the sign of . This duality extends to all moments of the hitting time. In two dimensions, the distribution of first-passage times to an absorbing circle in the radial velocity field again exhibits duality. Our approach also gives a new perspective on how varying the radial velocity is equivalent to changing the spatial dimension, as well as the transition between transience and strong transience in diffusion.